Determinants of energy futures—a scenario discovery method applied to cost and carbon emission futures for South American electricity infrastructure. (15th March 2019) - Moksnes, Nandi; Rozenberg, Julie; Broad, Oliver; Taliotis, Constantinos; Howells, Mark; Rogner, Holger
Abstract: Energy policy and investment are commonly informed by a small number of scenarios, modelled with proprietary models and closed data-sets. It limits what levels of insight that can be derived from it. This paper overcomes these critical concerns by exploring a large number of scenarios with an open-data and open-source model to address regional mitigation policy. Focusing on South America, we translate an ensemble of long-term electricity supply scenarios into policy insights and use post-processing methods to present a systematic mapping of solution outputs to model inputs. We find demand levels, the cost of capital and the level of CO2 -limits to be significant determinants of total investment cost. Low-carbon pathways are associated with low demand and low cost of capital. When cost of capital increases a shift away from wind and hydropower to natural gas and solar PV is seen. We further show that appropriate concessionary finance together with energy efficiency measures are critical—at a continental level—to unlock economic, low-carbon investment.